THE ROLE OF SOCIAL CAPITAL IN DISASTER RESILIENCE A COMPARATIVE STUDY OF URBAN AND RURAL AREAS - Oktaviany, Mega; Situmorang, Marningot Tua Natalis; Lansiwi, Muhammad Amin; Gymnastiar, Iman Ahmad; Saleh, Fitra (GoAcademica CRP, 2024)
This study explores the role of social capital in enhancing disaster resilience, comparing urban and rural areas to identify key differences and similarities. Social capital, encompassing networks, norms, and trust that facilitate coordination and cooperation, is crucial for communities facing disasters. Using a comparative study approach, we conducted surveys and interviews in selected urban and rural areas to gather data on social capital dimensions and their impact on disaster resilience. Our findings reveal that while both urban and rural communities benefit from social capital, the mechanisms and outcomes differ significantly. In urban areas, formal networks and institutional support play a more significant role, whereas in rural areas, informal networks and community cohesion are more influential. These differences highlight the need for tailored disaster resilience strategies that leverage the unique strengths of each context. The study contributes to the literature by providing empirical evidence on how social capital functions in diverse settings and offers policy recommendations to enhance disaster resilience through community engagement and capacity building.